Prolonged Duodenal Mucosal Lymphocyte Alterations in Patients With and Without Postinfectious Functional Gastrointestinal Disorders After Giardia Infection - Dizdar, Vernesa (J Infect Dis, 2019)
BACKGROUND: Persisting low-grade inflammation is suggested to play a role in postinfectious functional gastrointestinal disorders (PI-FGIDs). The present study examined alterations in duodenal mucosal lymphocytes during and after Giardia gastroenteritis in patients who did, or did not, develop PI-FGIDs. METHODS: Duodenal mucosal intraepithelial lymphocytes (IELs) and lamina propria CD3, CD4, CD8, and CD20 lymphocytes were quantified in 28 patients with chronic giardiasis (CG), 66 patients with persistent abdominal symptoms after acute Giardia infection (PI-FGID), 19 recovered controls (RCs), and 16 healthy volunteers (HCs). Associations with illness duration, abdominal symptoms, and histology grade were assessed. RESULTS: Duodenal CD4 IELs were significantly elevated in CG, then decreased, followed by an upward trend after 1 year in both the PI-FGID and RC groups. Duodenal lamina propria crypt CD4 T cells were decreased in CG, and stayed low for about 14 months before normalizing in both the PI-FGID and RC groups. Lamina propria CD20 cells were persistently elevated in all 3 Giardia-exposed groups. Biopsies with microscopic inflammation showed increased lamina propria CD20 levels. CONCLUSIONS: Duodenal mucosal lymphocyte alterations were prolonged after Giardia infection, but similar in patients who developed PI-FGID and recovered asymptomatic controls.